How develop intercultural curriculum in learning process. Some issues and considerations - Margiotta, Umberto (Formazione & insegnamento, 2015)
In both education in general and learning processes in particular, there is an increasing recognition of the need to develop students’ intercultural competence. The development of this competence poses a range of theoretical and practical challenges. In this article, it is emphasize the need of developing an intercultural curriculum, considering and discussing steps and dimensions of curriculum. It’s introduced an example of description of languages learning within an intercultural orientation and a model for understanding assessment. Consequently, it is introduced and discussed the construct, towards a conceptualisation. Following, it is considered the issues in eliciting intercultural competence in a proposed framework that includes assessment as both performance. The framework is composed by four interrelated processes Conceptualising (What to assess); Eliciting (How to elicit); Judging (How to judge) and Validating (How to justify). In the end, it’s emphasized the challenge put by the need of not just looking for easy ways to assess but to expand the repertoire of learning to accommodate a more complex view of processes learning that includes the development of intercultural competence.